Executive Committee Minutes 2008-08-28 - Academic Senate:::::::::
Accreditation Review Steering Committee – Selection of two faculty reps, Recommendation for revision to Non-Discrimination Policy, Faculty Eligible for Emeritus Status, Discussion of Diversity Council, Art Therapy Discontinuance